Implementación de un modelo de planificación de la producción y presupuestos agrícola en agrocasagrande s.a.c. - Cueva GutiérrezUTIÉRREZ, Jaime (2018)
This research work, entitled IMPLEMENTATION OF A PLANNING MODEL OF PRODUCTION AND AGRICULTURAL BUDGETS IN AGROCASAGRANDE S.A.C. in the city of Casagrande, 2018 has been developed with the purpose of establishing a planning based on sustainable methodologies and establishing a budget control in agricultural terms; for a timely decision making. The planning techniques to be used, the applied technology and implementation of Business Intelligence are established; through templates the data is integrated into the developed model; allowing visibility and comprehensive control of budgets. In this way, it was possible to carry out an evaluation and identification of the deviations of the budgets, concluding that, previously, a detailed control was not carried out and that it did not discriminate fields; therefore, the productivity of each field could not be identified. For this reason a planning model of production and agricultural budgets has been implemented by the planning team, following the methodology proposed, for a detailed evaluation of the budget components in agricultural terms, in order to identify the deviations, so as to allow the timely decision making at the productive field level.